THE CLASSROOM MANAGEMENT OF PHYSICAL EDUCATION TEACHERS IN BASIC EDUCATION - Reina, Fabio Tadeu; Felicio da Silva, Willian Gabriel [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This article aims to point out how the relationship between classroom management and the teaching of Physical Education content occurs. The purpose is, therefore, to know and better understand a set of teacher behaviors, usually grouped under the name of Classroom Management, dependent on a diverse set of beliefs and theoretical perspectives, on, among many other aspects, teaching, the teacher's roles and tasks. Thus, it is important to understand this existing relationship, in order to see how this teaching-learning process takes place with regard to the appropriation of specific knowledge of this school discipline by students. In this direction, to carry out this article, as a theoretical contribution, we use among other authors: Libaneo (2004), Paro (2007), Dal Prette (2007), Daolio (1994) and Brophy (2011); and to collect the data, that are analyzed later, we interviewed seven teachers of the elementary school II of Physical Education, effective in schools of the municipal public net of a city of the paulista interior, and as results of this research, among others aspects, we detach that the management of the classroom of the teacher of Physical Education, passes for its way of speaking, walk, dress, gesticulate, demonstrate a motor task, their behavior and their relationship with the students, in addition to the pedagogical practices that they carry out in school, all analyzed together with the contents that they may select to teach in their classes, something that appeared repeatedly in the speeches of the teachers with whom the research was developed.
Keywords: Classroom management; Physical education; Basic education; Teaching-learning process